Effects of Credentials, Competence, Career Levels and Professionalism on the Satisfaction among Nurses in Psychiatric Hospital, Surakarta Central Java, Indonesia - Suminanto, Suminanto; Istiatin, Istiatin; Sudarwati, Sudarwati (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Job satisfaction among nurses may be influenced by competency, education, income level, or the work environment, such as the type of facility, management, professional or career deve-lopment, and access to resources. The purpose of this study was to analyze the effect of credentials, competence, career levels, and professionalism on the satisfaction among nurses in mental hospital.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted in Surakarta, Central Java, from September to October 2022. A sample of 215 nurses from 22 Surakarta Mental Hospital was selected for this study. The dependent variable was satisfaction of nurses. The independent variables were credential, competence, career levels, and profesionalism. The data were collected by questionnaire and analyzed by a multivariate linear regression.Results: Education master or doctor (b= 0.05; 95% CI= 0.03 to 0.15; p= 0.02), income (b= 1.47; 95% CI= 0.10 to 0.78; p= 0.04), competence (b= 1.20; 95% CI= 0.07 to 0.32; p= 0.002), career levels (b= 1.08; 95% CI= 0.05 to 0.35; p= 0.007), professionalism (b= 0.22; 95% CI= 0.06 to 0.10; p= 0.005) increased satisfaction and it was statistically significant. Credentials (b= 1.11; 95% CI= 0.006 to 0.67; p= 0.08), increased satisfaction, but it was statistically non-significant.Conclusion: Job satisfaction among nurses increases with high career levels, good competence, good professionalism, good credential, education ≥Diploma III, and high income.Keywords: career levels, competence, credential, job satisfaction, professionalism, nurse.Correspondence:Suminanto. Masters Program of Management, Universitas Islam Batik Surakarta, Indonesia. Jl. Agus Salim 10, Sondakan, Laweyan, Surakarta, Central Java 57147. Email: mr.nannto@gmail.com. Mobile: +62 812-2606-925.Journal of Health Policy and Management (2023), 08(01): 23-29https://doi.org/10.26911/thejhpm.2023.08.01.03